2020
DOI: 10.1088/1361-6560/ab65db
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of fiducial marker visibility for MRI-only prostate radiotherapy simulation

Abstract: To objectively compare the suitability of MRI pulse sequences and commercially available fiducial markers (FMs) for MRI-only prostate radiotherapy simulation. Most FMs appear as small signal voids in MRI images making them difficult to differentiate from tissue heterogeneities such as calcifications. In this study we use quantitative metrics to objectively evaluate the visibility of FMs in 27 patients and an anthropomorphic phantom with a variety of standard clinical MRI pulse sequences and commercially availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…A limitation of this study is that it relies on the assumption that fiducial markers can be identified with good accuracy in MRI images. Much work has been done on the selection of optimal MRI sequences, optimal fiducial markers and detection methods for fiducial markers in MRI 10,18,19,35–37 . The goal of many of these studies was to identify fiducial markers for identification at simulation with the eventual goal of voxel burning the fiducial locations in DRR images for pretreatment positioning and alignment using C‐arm linacs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A limitation of this study is that it relies on the assumption that fiducial markers can be identified with good accuracy in MRI images. Much work has been done on the selection of optimal MRI sequences, optimal fiducial markers and detection methods for fiducial markers in MRI 10,18,19,35–37 . The goal of many of these studies was to identify fiducial markers for identification at simulation with the eventual goal of voxel burning the fiducial locations in DRR images for pretreatment positioning and alignment using C‐arm linacs.…”
Section: Discussionmentioning
confidence: 99%
“…The fiducials were identified based on the distinctive signal void and artifact that they produce on MRI 38,39 . The use of T 1 ‐weighted gradient echo‐based sequences has been published since this sequence produces distinctive artifacts for fiducial marker identification using only MRI simulation images 18,19 . In this study we used a T 1 ‐weighted MRI sequence to identify fiducials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Images were acquired without contrast administration. This sequence was used in this study because it quantitatively produces good gold fiducial marker visibility and has been used in previous MRI‐only detection workflows 12,19 . Patient setup at the MRI was performed using a knee wedge on a curved couch.…”
Section: Methodsmentioning
confidence: 99%
“…This sequence was used in this study because it quantitatively produces good gold fiducial marker visibility and has been used in previous MRI-only detection workflows. 12,19 Patient setup at the MRI was performed using a knee wedge on a curved couch. Patients were scanned using 18-channel anterior phased array coils (18-channel body coil, Siemens, Erlangen, Germany).…”
Section: A Patient Information and Image Acquisition Settingsmentioning
confidence: 99%